QTL mapping for biomass and physiological parameters linked to resistance mechanisms to ferrous iron toxicity in rice - Dufey, Inès; Hakizimana, Patrice; Draye, Xavier; Lutts, Stanley; Bertin, Pierre (Euphytica, 2009)
Lowland rice is often subject to iron toxicity which may lead to yield reduction. In order to cope with this nutrient disorder, plants have developed resistance strategies. The aim of this research was to assess morphological and physiological parameters linked to iron toxicity resistance mechanisms and to identify quantitative trait loci (QTLs) involved in their genetic determinism. A segregating population consisting of 164 recombinant inbred lines (RILs) derived from a cross between Azucena and IR64 was tested twice in hydroponics at the vegetative stage at 0 and 250 mg Fe²⁺ l⁻¹. Morphological traits were measured on all 164 RILs. Physiological traits, which were too time-consuming to allow their measurement on all the population, were measured on the two parents and extreme individuals only, selected on the basis of their leaf bronzing index and shoot dry weight. A total of 24 putative QTLs was identified on chromosomes 1, 2, 3, 4, 7 and 11 for leaf bronzing index, shoot water content, shoot and root dry weight, relative variation of shoot and root dry weight, shoot iron concentration, stomatal resistance and chlorophyll content index. Several QTLs were detected in overlapping regions for different parameters. The pertinence of phenotyping extreme RILs only for a QTL analysis is discussed in this study. The QTL analysis allowed to better understand the physiological response of rice in the presence of an excess of ferrous iron, inclusive the relations existing between the stomata closure, the shoot water content reduction and the oxidative stress linked to these growth conditions.